Edutainment Game to Improve Math Skills in Children Aged 4–5 Years - Putri Regina; Leny Marlina; Kurnia Dewi; Nyanyu Soraya; Yecha Febrieanitha Putri (Universitas PGRI Madiun, 2026)
The mathematical abilities of children aged 4-5 years at Chiqa Smart Kindergarten Palembang are not optimal, and their ability to improve their mathematical abilities is still low. In addition, the available learning media have not been utilized optimally. This study aims to develop valid, practical and effective edutainment game media to improve the mathematical abilities of children aged 4-5 years. This study uses the Research and Development research method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were class A at Chiqa Smart Kindergarten Palembang. Data collection techniques used observation, interviews, questionnaires and documentation. Data analysis techniques used validity tests, practicality tests and effectiveness tests. Validity and practicality data were obtained based on questionnaire data analyzed using a Likert scale, and effectiveness tests were obtained from hypothesis testing. Based on the results of the study, the validity of material experts was 94 in the very valid category, media experts 95 in the very valid category, and language experts 80 in the very valid category. The practicality test of edutainment games based on the teacher response questionnaire was 91.66 in the very practical category, as well as the student response questionnaire for small-scale trials of 72.61 stated practical and large-scale trials of 86.86 stated very practical. The effectiveness test of edutainment games was seen in the hypothesis test using the t-test; the hypothesis was obtained: tcount = 19.043, while ttable = 0.514. Because tcount > ttable, H_a is accepted and H_o is rejected. From the results of the t-test, a sig value of 0.001 was obtained, with the criteria of sig <0.05; it can be said that there is a significant difference in children before and after receiving treatment. So, edutainment games are effective in improving the mathematical abilities of children aged 4-5 years at Chiqa Smart Kindergarten Palembang. The results of this study concluded that edutainment games to improve mathematical abilities are declared valid, practical, effective and suitable for use in learning.